Brain tumor-initiating cells export tenascin-C associated with exosomes to suppress T cell activity. (3rd October 2018) - Mirzaei, Reza; Sarkar, Susobhan; Dzikowski, Lauren; Rawji, Khalil S.; Khan, Lubaba; Faissner, Andreas; Bose, Pinaki; Yong, V. Wee
ABSTRACT: The dismal prognosis of glioblastoma is attributed in part to the existence of stem-like brain tumor-initiating cells (BTICs) that are highly radio- and chemo-resistant. New approaches such as therapies that reprogram compromised immune cells against BTICs are needed. Effective immunotherapies in glioblastoma, however, remain elusive unless the mechanisms of immunosuppression by the tumor are better understood. Here, we describe that while the conditioned media of activated T lymphocytes reduce the growth capacity of BTICs, this growth suppression was abrogated in live co-culture of BTICs with T cells. We present evidence that BTICs produce the extracellular matrix protein tenascin-C (TNC) to inhibit T cell activity in live co-culture. In human glioblastoma brain specimens, TNC was widely deposited in the vicinity of T cells. Mechanistically, TNC inhibited T cell proliferation through interaction with α5β1 and αvβ6 integrins on T lymphocytes associated with reduced mTOR signaling. Strikingly, TNC was exported out of BTICs associated with exosomes, and TNC-depleted exosomes suppressed T cell responses to a significantly lesser extent than control. Finally, we found that circulating exosomes from glioblastoma patients contained more TNC and T cell-suppressive activity than those from control individuals. Taken together, our study establishes a novel immunosuppressive role for TNC associated with BTIC-secreted exosomes to affect local and distal T lymphocyte immunity.